Thermal degradation of dry kitchen waste: kinetics and pyrolysis products - Kumar M.; Srivastava N.; Upadhyay S.N.; Mishra P.K. (My University, 2025)
Pyrolysis of dry kitchen waste (KW) has been investigated using TGA/DTG, DSC, and lab-scale fixed-bed pyrolyser. Thermal characterization of the dry kitchen waste (KW) was carried out using standard protocols. The pyrolysis has been carried out at three different heating rates of 15, 20, and 40 °C/min from room temperature to 1000 °C. Kinetic analysis of the pyrolysis process using TGA data has been carried using iso-conversional model-free methods of Flynn-Wall-Ozawa (FWO), Kissinger–Akahira–Sunose (KAS), Tang, and Starink methods as well as model fitting method of Coats–Redfern. The pyrolysis for liquid yield (bio-oil) of pelletized KW was also performed at 400, 450, 500, 550, and 600 °C at a single heating rate of 15 °C/min in an inert atmosphere using a lab-scale fixed-bed pyrolyser. The maximum bio-oil yield (29.52%) was obtained at 500 °C. The FTIR results indicated the presence of alcoholic, phenolic, ester, and oxygenated group containing compounds, and GCMS results also indicated the presence of varying amounts of several organic molecules. The calorific value of the bio-oil was found to be 24 MJ/kg. Graphical abstract: [Figure not available: see fulltext.]. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.